Relapsed Symptoms in a Patient Treated for Pubic Symphysis Septic Arthritis/Adjacent Osteomyelitis: Diagnostic Challenges - Shankar Upadhyayula (Case Reports in Infectious Diseases)
We describe the case of a 14-year-old girl with relapsed pain following adequate treatment of pubic symphysis septic arthritis with adjacent osteomyelitis. Evaluation of her symptoms was challenging, because magnetic resonance imaging (MRI) was not helpful and repeat surgical exploration was not favored. She was treated with a combination of prolonged antimicrobial therapy and local steroid injection. This case highlights the limitations of MRI as a follow-up study for evaluating symptom relapse of acute osteomyelitis.